Perbandingan Pertumbuhan Jamur Aspergillus fumigatus pada Media PDA (Potato Dextrose Agar) dengan Alternatif Media dari Tepung Sagu Rumbia (Metroxylon Sagu): COMPARISON OF THE GROWTH OF ASPERGILLUS FUMIGATUS MUSHROOMS ON PDA MEDIA (PotatoDextrose Agar) WITH ALTERNATIVE MEDIA FROM RUMBER SAGO FLOUR (Metroxylon sago) - Asdinar Asdinar; Asrawati Asrawati; Adam Adam (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Background: Aspergillus fumigatus is a fungus that causes an opportunistic disease called Aspergillosis. Most tests used to determine the cause of fungal infections are carried out using the culture method. A popular growth medium for fungi is PDA media, which contains potato extract which is a source of carbohydrates. So that a substitute medium can be made that contains carbohydrates, sago flour is the highest carbohydrate producer, namely 84.7 grams per 100 grams of sago flour. Aim: To determine the comparison of the growth of Aspergillus fumigatus fungi on PDA media (potato dextrose agar) with alternative media from sago starch (Metroxylon sago). Method: This research methodology is pure experimentation with posttest only with control group design. Using the fungal culture method, with PDA media as control + and alternative media of sago starch sold at the Lambocca traditional market, Bantaeng, as test media with 3 concentration variants, namely concentrations of 12%, 14% and 16%. Result: Based on the findings of the research carried out, it can be concluded that five times the Aspergillus fumigatus treatment group was able to grow fungus which was grown in alternative media with concentration variants of 12%, 14%, 16%, and positive control. Conclusion: Media made from sago starch can be used as an alternative medium for growing Aspergillus fumigatus fungi. By looking at the average diameter of fungal colony growth at a concentration of 16% with an average of 10.85 mm, a concentration of 14% which is 9.3 mm and a concentration of 12% which is 7.5 mm. with the results of statistical tests, the p value = 0.000, which indicates there is a significant difference. Keywords: Aspergillus fumigatus, PDA, Sago flour